Perspectiva global de los combustibles sintéticos verdes: tecnologías, avances y desafíos en la transición energética - Orias-Rodríguez, Sebastián; González-Hernández, Jerson; González-Flores, Diego (Pontificia Universidad Católica del Perú, 2025)
Green synthetic fuels (from renewable sources and low emission) are produced from green hydrogen, combined with CO2 from sustainable sources or N2 from the air, using renewable energy. Various electrolyzer and reactor technologies enable the synthesis of products such as methane, methanol, ammonia, and even longer-chain hydrocarbons. Their main advantage with respect to the use of green hydrogen lies in the possibility of taking advantage of a large part of the existing infrastructure for its storage, transportation, and use. These characteristics position green synthetic fuels as a promising alternative for decarbonizing sectors that are difficult to decarbonize in industry and the global economy. This review outlines existing technologies to produce this type of fuel, focusing on their advantages, disadvantages, and applications at a global level. Understanding the development and expansion of these technologies is of great relevance for the creation and implementation of public policies in order to make informed decisions in the Latin American energy transition and promote the incorporation and innovation of these technologies.

Los combustibles sintéticos verdes (de fuentes renovables y bajas emisiones) se obtienen a partir de hidrógeno verde, combinado con CO2 de fuentes sostenibles o N2 del aire, utilizando energía renovable. Diversas tecnologías basadas en electrolizadores y reactores permiten la síntesis de productos tales como metano, metanol, amoniaco, e inclusive, hidrocarburos de cadenas más largas. Su principal ventaja con respecto al uso del hidrógeno verde radica en la posibilidad de aprovechar gran parte de la infraestructura existente para su almacenamiento, transporte y utilización. Dichas características posicionan los combustibles sintéticos verdes como una alternativa promisoria para la descarbonización de sectores difíciles de descarbonizar en la industria y en la economía global. Esta revisión se enfoca en la descripción de las tecnologías existentes para producir este tipo de combustibles centrándose en sus ventajas, desventajas y aplicaciones a nivel global. La comprensión del desarrollo y del auge de estas tecnologías es de gran relevancia para la creación e implementación de políticas públicas con el fin de tomar decisiones informadas en la transición energética Latinoamericana, así como para promover la incorporación e innovación en dichas tecnologías.
Global outlook for green synthetic fuels: technologies, advances, and challenges in the energy transition
Keywords: Synthetic fuels; Methanol; Methane; Ammonia; Gasoline; Electrolysis; CO2 capture; Metanol; Metano; Amoniaco; Gasolina; Electrólisis; Captura de CO2; https://purl.org/pe-repo/ocde/ford#1.04.00